(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
This article examines the impact of high-voltage power lines on agricultural land, with a focus on conservation areas and agricultural sustainability. Potential hazards are addressed, such as electromagnetic effects on plants and animals, as well as possible damage to equipment and difficulties when cultivating fields near power lines. The article also examines measures taken to ensure the safety and sustainability of agricultural land, including the establishment of conservation zones and balancing the need for electricity with the need to maintain land productivity. The authors discuss the importance of finding a balanced approach to this issue to benefit both the agricultural sector and energy sustainability.